The West Indian Peridinetini (Coleoptera: Curculionidae: Baridinae) - Prena, Jens (Zootaxa, 2009)
Two genera and nine species of Peridinetini are recognised in the West Indies; four of the species are newly described. Peridinetus Schönherr is represented in the Greater Antilles by P. concentricus (Olivier), P. decipiens Prena sp. n., P. fuscosignum Prena sp. n., P. poeyi Jacquelin du Val stat. res., P. roeselii (Boheman) and P. sexguttatus (Fabricius) comb. n. and Palliolatrix Prena in the Lesser Antilles by P. insignis (Chevrolat), P. lateropicta Prena sp. n. and P. silacea Prena sp. n. Ephimerus Schönherr is synonymised with Peridinetus (syn. n.). The overlooked synonymy of Peridinetus signatus Rosenschöld with P. concentricus is reinstated. Habitus images, distribution maps and a key for identification are provided.